Efficacy of options to address balancing challenges: Integrated gas and electricity perspectives. (15th March 2017) - Qadrdan, Meysam; Ameli, Hossein; Strbac, Goran; Jenkins, Nicholas
Highlights: Variability of wind power poses operational challenges to power system. Roles of three options to address the operational challenges were evaluated. Electricity storage was shown to minimise energy losses due to wind curtailment. The flexibility options reduce the gas and electricity networks' operating costs. Abstract: Integration of a large capacity of wind generation in the Great Britain (GB) electricity network is expected to pose a number of operational challenges. The variable nature of wind generation necessitates introduction of technologies that can provide flexibility to generation portfolios and therefore compensate for intermittency of wind generation. In this paper, the efficacy of three options to address electricity balancing challenges was evaluated: flexible gas-fired plants, electricity storage and Power-to-Gas system. The combined gas and electricity network model (CGEN) was enhanced and through adopting a rolling optimisation approach the model aims at minimising the operational cost of an integrated gas and electricity networks that represents a GB system in 2030. The potential impacts of employing each of the flexibility options on the operation of the integrated electricity and gas networks were investigated. The analysis showed that amongst all the flexibility options, the deployment of grid-scale electricity storage will achieve the highest reduction in the operational cost of the integrated system (£12 million reduction in a typical winter week, and £3 million reduction in a typical summer week). The results of this study provide insights on the system-wide benefits offered by each of the flexibility options and role of the gas network in the energy system with large capacity of wind generation.